2015
DOI: 10.1039/c4ee03664f
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the rate-dependent J–V hysteresis, slow time component, and aging in CH3NH3PbI3 perovskite solar cells: the role of a compensated electric field

Abstract: Ionic displacement modifying the electric field in the device is found as most likely reason for the hysteresis which is examined by separating fast and slow processes and comparing devices with and without blocking layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

88
1,168
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 1,229 publications
(1,261 citation statements)
references
References 37 publications
88
1,168
4
1
Order By: Relevance
“…To date, many reasons have been indicated to be the causes of hysteresis behavior, such as ion migration and transient ferroelectric polarization [44]. On the other hand, any factor disadvantageous to charge transfer kinetic processes can also result in pronounced hysteresis, like serious charge recombination, slow transport, and less efficient interfacial charge extraction [45,46]. Herein we focus specifically on revealing the influence of ETL underlayer on the hysteresis behavior.…”
Section: Resultsmentioning
confidence: 99%
“…To date, many reasons have been indicated to be the causes of hysteresis behavior, such as ion migration and transient ferroelectric polarization [44]. On the other hand, any factor disadvantageous to charge transfer kinetic processes can also result in pronounced hysteresis, like serious charge recombination, slow transport, and less efficient interfacial charge extraction [45,46]. Herein we focus specifically on revealing the influence of ETL underlayer on the hysteresis behavior.…”
Section: Resultsmentioning
confidence: 99%
“…[76] Although the defect passivation process significantly enhances the device performance and decreases the hysteresis, it is found that the time interval for charge trapping and detrapping ranges within milliseconds, [157] or even nanoseconds, [158] which is much shorter than the typical time for the hysteretic behavior. [159] The slow processes, such as the giant switchable photovoltaic effect and the very slow (seconds range) increase in photocurrent after poling, cannot be explained by a charge trapping mechanism alone. [131] Van Reenen et al [157] recently proposed that rather than having a single origin, the hysteresis has to be interpreted in terms of a combination of factors, including 1) charge trapping/detrapping and 2) the ionic migration, which will be discussed in the following section.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Current-voltage (J-V) curves were recorded by applying a forward bias with a scan rate of 10 mV s À1 in order to minimize the hysteresis effects stemming from the perovskite material. [38] Hysteresis scans showing the performance under forward and reverse bias can be found in the SI. The results show excellent performances for all the benzotrithiophene derivatives, being BTT-3 slightly better than its analogous BTT-1 and BTT-2.…”
mentioning
confidence: 99%